Estudio De Caso: Turismo Comunitario. Nivel De Satisfacción del visitante Sumak Kawsay, Provincia de Chimborazo - Ecuador - Jenry Ernesto López Romero; Rita Sulema Lara Vásconez; Manuel Antonio Abarca Zaquinaula; Luis Rafael Fiallos Ortega Norma; Norma Lissette Naranjo Sánchez; Rafael Marcos López Romero (European Scientific Journal, ESJ, 2018)
Ecuador is the country with the most widely diversified land mass per square mile in the whole world. It has countless live ecosystems and cultures, and it contains 11% of the world’s biodiversity. These conditions have resulted to the development of the most interesting touristic activities. The province of Chimborazo is located at the very center of the Inter-Andean Highway and is known as the “Province of the Tall Peaks.” The tallest of which is the volcano Mt. Chimborazo with a height of 6,310 mts (20,700 ft.). It, however, gave its name to the province itself. The train that runs down through the center of Ecuador to the Devil’s Nose Mountain makes the province optimum for touristic activity. The small city of Calpi is one of the best known historic areas of Riobamba County. This is because in its interior, there are a lot of natural attractions for tourists. The community which is known as “The Royal Palace” tries to conserve its natural resources as well as to preserve its natural identity. During the past few years, this community has developed a lot of touristic activity since the Plan for Touristic Development is being organized for that zone. Tourism is being considered as an activity for the productive development that will augment and strengthen the local economy.